FARMERS EMPOWERMENT ON FOOD SECURITY PROGRAM IN ENGGAL MAJU FARMERS GROUP ASSOCIATION OF KEBUMEN REGENCY - Ahmad Muhtarom; Teguh Djuharyanto; Adhi Iman Sulaiman (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
Agriculture is a strategic sector in national development because it plays an important role infood availability and realizes food security. The Farmer's attitude is one of the determining aspects toinvolvement farmers in empowerment programs for food security. A research, aiming to describe thefarmer's attitude and analyze the farmer's attitudes and the influence factors that influence the farmer'sattitudes on the food security empowerment program. The research used mixed method, the number ofresearch respondents was 60 farmers members of the farmer's group association Enggal Maju KebumenDistrict, determined by cluster random sampling, and for qualitative data, the informants were selectedpurposively. The Farmer's attitude analyzed with descriptive analysis and the influence factors offarmers' attitude used multiple linear regression analysis. Farmer's attitude analyzed with descriptiveanalysis and the influence factors of farmer's attitude used multiple linear regression analysis. Theresult show that the farmer's attitudes in terms of cognitive, affective, and conative components towardthe objectives program were high, farmer's attitudes towards, the target, implementation, and benefits ofthe program were very highly classified. Farm size, personal experience, and the influence of the important people were a significant effect on the farmer's attitudes in food security empowermentprograms. The need to maximize the function of farmer’s groups, consistency of extension workers,agencies and heads of Gapoktan assist and guide farmers so that the sustainability of activities ismaintained